The Impact of The Digital Economy on Macroeconomic Growth and Stability Post-Pandemic for Society - Kharinatul Hanani (CV Pena Jaya Pers, 2025)
The COVID-19 pandemic has catalyzed the acceleration of the digital economy globally. Mobility restrictions and disruptions to conventional economic activities have forced governments, businesses, and the public to rapidly adopt digital technology. This article aims to analyze the impact of the digital economy on economic growth and macroeconomic stability during the pandemic. The method used is a library study, examining academic literature, reports from international institutions, and policy publications related to the digital economy and the pandemic. The study's results indicate that the digital economy plays a crucial role in maintaining economic growth amidst the global contraction by increasing productivity, sustaining business activity, and promoting digital financial inclusion. However, the